Extended persistence of antiphospholipid antibodies beyond the 12‐week time interval: Association with baseline antiphospholipid antibodies titres. (15th September 2019) - Devignes, Jean; Smaïl‐Tabbone, Malika; Hervé, Alex; Cagninacci, Geoffroy; Devignes, Marie‐Dominique; Lecompte, Thomas; Zuily, Stéphane; Wahl, Denis
Abstract: Introduction: The confirmation time interval for the presence of antiphospholipid antibodies (aPL) has been extended to 12 weeks as epiphenomenal antibodies may disappear after 6 weeks. Our aim was to analyse extended persistence of aPL positivity beyond the 12‐week interval. Methods: We retrospectively analysed our database of 23 856 aPL test samples collected between 2005 and 2017 from 17 367 consecutive patients. Two groups of patients were identified among aPL‐positive patients, confirmed at 12 weeks: with or without extended persistence beyond confirmatory testing. Percentages of extended persistence are given according to the initial aPL positivity profiles, and baseline laboratory variables are compared between the two groups. Results: Three hundred and twenty‐seven patients confirmed aPL‐positive had subsequent testing. The vast majority of them displayed extended persistence in the long term: 89.6% and up to 97.9% for patients with initial triple positivity. In extended persistent positive patients, there were more LA‐positive initial samples, and baseline LA test values and IgG aCL titres were higher than in nonpersistent positive patients. Conclusion: Data from a large database of an aPL referral laboratory showed that the time interval of 12 weeks defining persistence of aPL positivity was appropriate for the majority of patients. Furthermore, we found baseline features associated with extended persistence.